DIETARY FIBRE IN CEREAL GRAINS – A REVIEW - Fraś, Anna; Gołębiewska, Kinga; Gołębiewski, Damian; Boros, Danuta (Plant Breeding and Seed Science, 2018)
The article presents basic information on dietary fibre, including its current definition and characteristics of individual components. The physiological and health-promoting effects of soluble and insoluble fractions of fibre, are also presented. The characteristics of dietary fibre are discussed, taking as examples the selected cereal species most popular in Poland and in Europe which make up a significant part of the diet and, as such, are an important source of this component.